Satellite-based assessment and in situ validation of solar irradiation maps in the Republic of Djibouti. (October 2015) - Pillot, Benjamin; Muselli, Marc; Poggi, Philippe; Dias, João Batista
Highlights: We have computed solar irradiation maps over Djibouti from the OSI SAF satellite model. Ground measurements were carried out between 2010 and 2013 throughout the country. Statistical study between estimates and measurements has validated model's accuracy. Mean irradiation maps expose significance and consistency of the solar potential. Abstract: As well as for Sub-Saharan Africa, solar energy presents many relevant standalone applications for remote populations of the Republic of Djibouti. Therefore, in order to estimate the significance and the distribution of the solar resource throughout the country, we have retrieved the first hourly global irradiation maps of the country, at 0.05 ° resolution and for the period 2008–2014, using the OSI SAF satellite-derived model. To assess the accuracy of this solar atlas, we have then compared estimates with ground measurements collected between 2010 and 2013 by temporary weather stations carried out on 4 different sites. The results of this comparison have shown a good precision of the global process, with for the daily irradiation a maximum relative error of 8.05% and a minimum correlation coefficient of 0.8892. Finally, the solar irradiation maps extracted from the atlas show the solar potential is substantial with a daily mean irradiation equal to 5.92 kW h / m 2, and also spatially and temporally consistent, with a daily standard deviation of 0.216 kW h / m 2 and a yearly range between 5.08 kW h / m 2 day and 6.69 kW h / m 2 day .